Desconstruindo Amélias: musicoterapia com mulheres em situação de violência doméstica sob a ótica da teologia feminista - Krob, Daniéli Busanello (2013)
This research is based on the application of Music Therapy to treat the emotional damage resulting from domestic violence, based on theories, concepts and methods of Feminist Theology. The opening sentence of the title Deconstructing Amelia was inspired by the song of the same name, composed by Pitty and Martin (2008). Many women who have suffered domestic violence go through this process of deconstructing their Amelias interiors, then to rise again as free women, selfconfident, independent, strong and empowered in all her femininity to be just women, without any label or stereotype. To account for the proposed theme for this dissertation was made a bibliographical research and social research. In terms of methodology, the research can be defined as an action research of a qualitative nature, approved by the Ethics Committee of the Colleges EST, as required by resolution 196/96 of the National Health Council. Its main objective was to investigate how Music Therapy and Feminist Theology can reframe the emotional damage resulting from domestic violence. Specifically, we sought to investigate the extent to which funds Music Therapy are effective to minimize or cure depression and anxiety states of women in situations of domestic violence, as well as investigate the extent to which Music Therapy can be applied to raise self-esteem and fostering the autonomy and re-socialization of the target population of this research. Finally, we sought to understand the religious discourse and its relation to the behavior of women who experienced domestic violence. It was found that Music Therapy can be an effective tool to treat the emotional damage in women due to domestic violence. The particularity of music as nonverbal language assists a lot in the process, because the trauma in an unconscious way. However, to make use of Music Therapy as a tool for emotional rehabilitation of women who have experienced domestic violence, you should always be with a look directed to gender issues, making it a Music Therapy with feminist perspectives. At this point, Feminist Theology contributed solidly. It was also concluded that participants who receive spiritual advice obtained only negative or omission of his Church, had worse outcomes than participants who received support from their spiritual leaders or just did not look for any Church.